On the content of prepositions in prepositional collocations - Sicherl, Eva (ELOPE (Ljubljana), 2004)
Th e article aims to shed some light on the problems faced by non-native speakers in the formation of so-called prepositional collocations (i.e. typical, recurrent combinations of verbal, nominal or adjectival bases with prepositional collocators). Th e reasons for frequent mistakes mainly lie in the meaning of the preposition used as part of collocation, which tends to be even more dispersed, abstract and diffi cult to defi ne than that of the preposition used in a free combination. However, the preposition when used as a collocator seems to act, at least to some extent, as a carrier of some content; this can be proven by valency patterns: meaning-related content words(collocational bases) tend to regularly combine with identical prepositions. Th e fact that prepositions used in collocations also have theirsemantic part to contribute to the whole unit should also be considered in the classifi cation of collocations into grammatical and lexical ones.
Keywords: angleščina; kolokacije; kontrastivna lingvistika; predlog; predložna zveza; prevajanje; slovenščina; slovnica; vezljivost